Sex-Specific differences in running injuries: a systematic review with meta-analysis and meta-regression - Hollander, Karsten Peter; Rahlf, Anna Lina; Wilke, Jan; Edler, Christopher; Steib, Simon; Junge, Astrid; Zech, Astrid (Sports medicine, 2021)
Running is a popular sport with high injury rates. Although risk factors have intensively been investigated, synthesized knowledge about the differences in injury rates of female and male runners is scarce.
Published 12 January 2021
Gesehen am 12.07.2022